Automatic Temperature and Humidity Regulation System Design for Oyster Mushroom Growth - Kadek Reda Setiawan Suda; I Wayan Arsa Suteja; Made Adi Surya Antara; I Gede Eka Wiantara Putra; Ida Bagus Putu Wija (TEPIAN, 2025)
Oyster mushrooms are safe for consumption. The growth of mushrooms in mushroom houses is highly dependent on physical factors such as temperature, humidity, light, pH of the growing medium, and aeration. In this paper researcher concern research physical factors of temperature as a control growth of mushrooms in mushroom houses. The temperature in the mushroom house is very important to note because temperature is one of the factors that affects the performance of enzymes and the metabolism of oyster mushrooms. By implementing automatic temperature and humidity control in mushroom houses, the quality of oyster mushroom harvests can be improved and the income of local oyster mushroom farmers can be increased, thereby helping the government in increasing regional income. The results obtained from this automatic control are that the automatic temperature and humidity device was successfully made according to the design. Furthermore, the results of the tool testing, namely for the electronic tool expert test, obtained 95.45% in very decent qualifications, the results of the small group test were 90.85% in very good qualifications, and the results of the large group test were 91.80% in very good qualifications. The temperature and humidity control device can be of positive benefit to the community, especially to oyster mushroom farmers.